Photovoltaic System With Sun-Tracker - Riabov, Mikhail (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
The aim of the semestral work "Photovoltaic system with sun-tracker“ is to apprise with principles of operation of solar systems. We will focus on the tracking system, which is turning itself depending on the position of the sun. In the theoretical part we will describe the principle of operation of photovoltaic cells and solar systems. In the practical part of the work we will compare the parameters of the static and dynamic solar system and make decision, which of these systems is more profitable for use.
Keywords: Solar radiation; VA characteristics; photovoltaic cell; p-n transition; solar system